MicroRNAs as Important Players in Host–Adenovirus Interactions - Piedade, Diogo; Azevedo-Pereira, José M. (Frontiers in Microbiology, 2017)
MicroRNAs (miRNAs) are powerful regulators of gene expression and fine-tuning genes in all tissues. Cellular miRNAs can control hundreds of biologic processes (e.g. morphogenesis of embryonic structures, differentiation of tissue-specific cells and metabolic control in specific cell types) and have been involved in the regulation of nearly all cellular pathways. Inherently to their involvement in different physiologic processes, miRNAs deregulation has been associated with several diseases. Moreover, several viruses have been described as either, avoid and block cellular miRNAs or synthesise their own miRNA to facilitate infection and pathogenesis. Adenoviruses genome encodes two non-coding RNAs, known as viral-associated (VA) RNAI and VA RNAII, which seem to play an important role either by blocking important proteins from miRNA pathway, such as Exportin-5 and Dicer, or by targeting relevant cellular factors. Drastic changes in cellular miRNA expression profile are also noticeable and several cellular functions are affected by these changes. This review focuses on the mechanisms underlying the biogenesis and molecular interactions of miRNAs providing basic concepts of their functions as well as in the interplay between miRNAs and human adenoviruses.